Pengalaman Aktivitas Spiritual pada Orang dengan HIV/AIDS (ODHA) dalam Menjalani Proses Penyakitnya - Chiyar Edison; Setyowati Setyowati; Agung Waluyo (Faletehan Health Journal, 2021)
Spiritual well-being is a domain affecting the outcome of antiretroviral therapy in PLWH. However, spiritual need recently is still not adequately fulfilled in health service system. Therefore, it is essential to recognize the spiritual experience in PLWH to identify the depiction of their needs. This descriptive phenomenological study aimed to explore the spiritual experience of PLWH in the disease process by involving five participants in in-depth interviews. The thematic content analysis resulted five themes, namely (1) Obtaining guidance, being more religious, being more afraid of sin, more diligent in praying and reading the holy book; (2) Surrender and accept the illness because this is a warning, test and power of Allah; (3) Support from mother by encouraging to recitation and reminding to dhikr; (4) Experiencing sadness, shock, blaming others so that they want to end their life and avoid other people; (5) The participants hope to be healthy in this world and lucky in the hereafter. This study recommended further studies quantitatively and the assessment of PLWH spirituality in the nursing care practice.